Fragilariopsis cylindrus Helmcke et Krieger - Al-Handal, Adil Y.; Torstensson, Anders; Wulff, Angela (Zenodo, 2022)
Fragilariopsis cylindrus (Grunow ex Cleve) Helmcke et Krieger (Figures 91, 92, 115, 116) Literature: (Hasle 1965, p. 34, fig. 12:6–12; Snoeijs and Vilbaste 1994, p. 50, fig. 138; Witkowski et al. 2000, p. 360, pl. 213, figs. 8–14). Description: Length 5–11 µm, width 2–3 µm, striae 15–20 in 10 µm, fibulae 15–20 in 10 µm. Ecology and distribution: A common bipolar sea-ice diatom, particularly in summer and autumn (Kang and Fryxell 1992) but also found in brackish-water of the Baltic Sea, forming ribbon-like colonies (Snoeijs and Vilbaste 1994). Fragilariopsis cylindrus has been used as an indicator species for sea-ice movement in both polar regions (von Quillfeldt 2004). It was not observed in Potter Cove during the previous collection. Rare in the material examined. Published as part of Al-Handal, Adil Y., Torstensson, Anders & Wulff, Angela, 2022, Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms, pp. 81-103 in Botanica Marina (Warsaw, Poland) (Warsaw, Poland) 65 (2) on page 95, DOI:10.1515/bot-2021-0066, http://zenodo.org/record/11000147